Refractory status epilepticus responding to lidocaine: a case report - Özer, Gökhan (The European Research Journal, 2018)
Status epilepticus is a life-threatening condition, which is associated with a high mortality and morbidity when left untreated. It is defined as a continuous seizure lasting more than 30 min or successive seizures with no recovery between any of them. Mortality of status epilepticus depends on the duration and type of seizure, concomitant diseases and age of the patient. Managament of status epilepticus includes ensuring adequate airway, stabilization of circulation and use of antiepileptic drugs. Benzodiazepines, phenobarbital, phenytoin, fosphenytoin, general anesthesia and lidocaine are used for the treatment of status epilepticus. Here, we discuss a patient with refractory status epilepticus who achieved a very good response and full recovery only with lidocain infusion among all forms of therapy given.